2016
DOI: 10.1111/obr.12470
|View full text |Cite
|
Sign up to set email alerts
|

Environmental interventions for altering eating behaviours of employees in the workplace: a systematic review

Abstract: Environmental, or 'choice-architecture', interventions aim to change behaviour by changing properties/contents of the environment and are commonly used in the workplace to promote healthy behaviours in employees. The present review aimed to evaluate and synthesize the evidence surrounding the effectiveness of environmental interventions targeting eating behaviour in the workplace. A systematic search identified 8157 articles, of which 22 were included in the current review. All included studies were coded acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 48 publications
(48 reference statements)
4
100
1
1
Order By: Relevance
“…Salience through point-of-purchase signs and messages is often part of multicomponent interventions, and in combination with increased availability, presentation or price reduction effects on healthy choices are larger (e.g., Escaron et al 2013;Kahn-Marshall and Gallant 2012). Such interventions limit the assessment of their individual contribution (Allan et al 2017). More focused reviews, however, show that specific approaches can be effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salience through point-of-purchase signs and messages is often part of multicomponent interventions, and in combination with increased availability, presentation or price reduction effects on healthy choices are larger (e.g., Escaron et al 2013;Kahn-Marshall and Gallant 2012). Such interventions limit the assessment of their individual contribution (Allan et al 2017). More focused reviews, however, show that specific approaches can be effective.…”
Section: Discussionmentioning
confidence: 99%
“…The emerging field of active and deliberate design of settings and contexts for healthier choices has been covered in several recent reviews that often vary in their definitions of nudging and choice architecture (e.g., Arno and Thomas 2016;Broers et al 2017;Bucher et al 2016;Wilson et al 2016). Some of these reviews focus on specific settings such as schools (Nørnberg et al 2015), universities (Roy et al 2015), and self-service settings (Skov et al 2013); others cover workplace interventions (Allan et al 2017) or children in their home environment (Lycett et al 2017). Other reviews focus on specific ways food is presented, such as type of tableware (e.g., Holden et al 2016), or have not focused on choice but rather included relevant literature while reviewing a wider set of interventions to foster healthier choices (e.g., Hillier-Brown et al 2017;Kahn-Marshall and Gallant 2012).…”
Section: General Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between dietary intervention and attitude towards diet was only reported in one medium quality SR which concluded that results were not very strong, however, small positive results were reported (22) . Self-efficacy was reported in one SR (1) and food purchasing patterns were reported in five SRs (1,4,15,16,18) , however, the number of studies that reported on these outcomes was relatively small so that no conclusion could be made and further evidence is needed. Overall, changes, although positive, were small and the potential impact as well as long-term effectiveness on diet and health is unknown.…”
Section: Diet-related Outcomesmentioning
confidence: 99%
“…Limitations from previous interventions  Low participation rates (11,12) and high attrition rates (19)  Lack of thorough description of intervention content and delivery (9,15,18)  Self-reported diet measures may have introduced bias and impact on validity of results (5,13,20)  Evidence supported that workplace interventions provided benefits in the short-term (4,16,20) , however, information on long-term benefits was missing (1,11,15,19)  Selection bias in studies, i.e. self-selected volunteers rather than the whole workplace that may have skewed results (11,13)  Lack of cost-saving evaluation reported in studies (14,20) Recommendations for future interventions Designing interventions  Obtain management support and commitment as this is key for intervention success (8,16,19)  Maximize participation rates and intervention adherence (11,12,16)  Involve employees in planning, implementation, management (11,16)  Plan for a longer study duration (11) -recommendations ranged from at least six months (19,21) to 12 months (1,9)  Develop intervention based on an underlying behaviour change theory and explain reasoning (9)(10)(11)  Intervene at multiple levels (e.g.…”
mentioning
confidence: 99%